Pengaruh Profitabilitas, Likuiditas dan Leverage terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderating (Studi pada Perusahaan Ritel di BEI) - Dewi, Nila Sandi Alifia; Khuzain, Khuzain; Djawoto, Djawoto (Jurnal Bisnis dan Manajemen, 2023)
This study aimed to investigate the effect of profitability, liquidity, and leverage on firm value with dividend policy as a moderating variable in retail companies listed on the Indonesia Stock Exchange. Therefore, it applied a quantitative design with secondary data, including financial reports from 2015 2019 in balance sheets and income statements from the Indonesia Stock Exchange. This study used a purposive sampling research technique, so the research samples were seven retail companies listed on the Indonesia Stock Exchange. While the data analysis method used moderating regression analysis (MRA). The results of the study using MRA indicated that the profitability variable (return on assets) had a positive and insignificant effect on firm value (price book value); the liquidity (current ratio) had a positive and significant effect on firm value (price book value); and the leverage (debt to equity ratio) had a positive and insignificant effect on firm value. Moreover, the profitability had a positive and insignificant effect on firm value moderated by dividend policy (dividend payout ratio), and the liquidity and leverage had a negative and insignificant effect on firm value moderated by dividend policy